Pengaruh Total Aset dan Liabilitas terhadap Laba Perusahaan pada PT ABM Investama Tbk - Anisa, Anisa; Mailindra, Wiyan; Patria, Nelli (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the effect of total assets and liabilities on company profits at PT ABM Investama Tbk. The data used in this research is in time series form using the financial reports of PT ABM Investama Tbk for the period 2013-2022. Using quantitative descriptive methods using secondary data with multiple regression analysis tools. The results of this research show that there is a significant influence on total assets and liabilities on profits at PT ABM Investama Tbk during the 2013-2022 period.